Berechnung der Abstrahldämpfung in ebenen Wellenleitern aufgrund eines angrenzenden Fluids - Kiefer, Daniel A.; Ponschab, Michael; Rupitsch, Stefan (Fortschritte der Akustik - DAGA 2018, 2018)
Geführte Wellen in Platten, insbesondere Lamb-Wellen, werden zur zerstörungsfreien Werkstoffprüfung eingesetzt sowie in ultraschallbasierten Messsystemen gezielt angeregt und genutzt. Wesentlich für den Entwurf solcher Systeme ist die Kenntnis der Dispersionskurven, die den Zusammenhang zwischen Frequenz und sich ergebenden Wellenzahlen wiedergeben. Obwohl die Rayleigh-Lamb-Gleichungen diesen Zusammenhang analytisch beschreiben, sind numerische Verfahren zur Lösung stets notwendig, da die Gleichungen transzendent sind. Während klassischerweise ein Nullstellensuchverfahren angewandt wird, wurden neuerdings Verfahren entwickelt, welche auf der Diskretisierung der Bewegungsdifferentialgleichungen beruhen. Diese arbeiten deutlich stabiler und zuverlässiger. Dabei werden die Rayleigh-Lamb-Gleichungen nicht explizit gelöst, sondern der Dispersionszusammenhang auf ein Eigenwertproblem zurückgeführt. Für den Fall der freien Platte kann dieses mit den üblichen numerischen Methoden einfach und effizient gelöst werden. In der Praxis grenzt jedoch oft ein Fluid an die Platte an. Eine Lamb-Welle gibt dann Energie an die Umgebung ab, was für viele Anwendungsfälle kritisch ist. Die Lamb-Welle erfährt dadurch eine Abstrahldämpfung, welche durch den Imaginärteil der Wellenzahl beschrieben wird. Die Randbedingungen für die Platte führen in diesem Fall zu einem nichtlinearen Eigenwertproblem, für das kein etabliertes Lösungsverfahren existiert. In diesem Beitrag wird eine Lösungsmethodik im Sinne einer Fixpunktiteration präsentiert, sowie Ergebnisse vorgestell
Keywords: Lambwellen; Abstrahlung; Spektrale Kollokation; Fluidbelastete Platte

Berechnung der Auswirkung mechanischer Spannungen auf die Ausbreitung von Lamb-Wellen - Ponschab, Michael; Kiefer, Daniel A.; Rupitsch, Stefan (Fortschritte der Akustik - DAGA 2019, 2019)
Mechanische Spannungen in einem Festkörper beeinflussen die Ausbreitung elastischer Wellen. Dieser nichtlineare Effekt wird als Akustoelastizität bezeichnet und wurde für Volumenwellen ausführlich behandelt. Seit einigen Jahren wird auch die Auswirkung auf die Ausbreitung geführter Wellen in üblicherweise eine Methode zur Nullstellensuche oder eine Finite-Elemente-Methode eingesetzt. Ein alternativer numerischer Ansatz zur Berechnung der Dispersion von Lamb-Wellen basiert auf der spektralen Kollokationsmethode. Dieses Verfahren konvergiert schneller als die anderen Methoden und ist unkompliziert zu implementieren. In diesem Beitrag werden geführte Wellen in einer mechanisch vorgespannten Platte modelliert und mittels spektraler Kollokationsmethode berechnet. Die resultierenden Änderungen der Phasen- und Gruppengeschwindigkeit stimmen sehr gut mit Literaturergebnissen überein und werden erörtert. Spannungsgradienten über die Plattendicke, wie sie beispielsweise durch Biegemomente hervorgerufen werden, bereiten bei der Modellierung Schwierigkeiten. Solche Spannungsgradienten wurden bisher durch Schichten mit homogener Spannung angenähert, wodurch Gradiententerme in den zugrunde liegenden Gleichungen vernachlässigt wurden. Wie der Einfluss von Biegemomenten auf die Wellenausbreitung einer Platte ohne diese Vereinfachung mit Hilfe der spektralen Kollokation berechnet werden kann, wird ebenfalls in diesem Beitrag vorgestell
Keywords: Akustoelastischer Effekt; Lamb-Wellen; Geführte Welle

Berechnung der vollständigen Dispersionscharakteristik von abstrahlenden Lambwellen mittels Variablentransformation - Kiefer, Daniel A.; Ponschab, Michael; Rupitsch, Stefan (Fortschritte der Akustik - DAGA 2019, 2019)
Entlang einer Platte können sich unterschiedliche geführte mechanische Wellen ausbreiten, darunter sogenannte Lambwellen. Grenzt ein Fluid an die Platte an, so ändern sich im Allgemeinen die Ausbreitungseigenschaften dieser Wellen erheblich. Dies ist darauf zurückzuführen, dass Energie von der Platte in das Fluid übergeht und dort eine akustische Welle anregt. Für Anwendungen ist häufig die Interaktion zwischen Platte und Fluid maßgeblich. Diese Interaktion kann als abstrahlende Lambwelle modelliert werden und führt zu einem nichtlinearen Eigenwertproblem, welches aus numerischer Sicht schwer zu lösen ist. In diesem Beitrag wird eine Variablentransformation vorgestellt, die das Problem auf ein polynomielles Eigenwertproblem zurückführt. Dies erleichtert das Lösen, da polynomielle Eigenwertprobleme durch Überführen in einen höherdimensionalen Zustandsraum als lineares Eigenwertproblem aufgefasst werden können. Für Letztere existieren hoch effiziente und robuste numerische Lösungsmethoden, die somit nach Anwenden der vorgeschlagenen Transformationen direkt zur Berechnung von abstrahlenden Lambwellen eingesetzt werden können. Im Gegensatz zu konventionellen Nullstellensuchverfahren findet die vorgestellte Methode zuverlässig alle Moden der fluidbelasteten Platte. Wie die resultierenden Dispersionskurven zeigen, können sich die Lösungen erheblich von denen der freien Platte unterscheiden. Die Ergebnisse wurden mit anderen Berechnungen verglichen und zeigen eine sehr gute Übereinstimmung.

Calculating the full leaky Lamb wave dispersion characteristics - Kiefer, Daniel A.; Ponschab, Michael; Rupitsch, Stefan (Journal of the Acoustical Society of America 145(3), 2019)
Lamb waves are mechanical waves guided in a plate with stress-free boundaries. In practice, the plate is often in contact with a fluid. The propagation of guided waves may change substantially in this case due to interaction with the adjacent medium, e.g., acoustic radiation may lead to leakage of energy into the fluid domain. The resulting plate modes are called leaky Lamb waves, and their attenuation due to leakage is an important parameter for the design of ultrasonic devices that exploit such waves. Modern methods to calculate dispersion characteristics of guided waves, i.e., the wavenumber-frequency relationship, solve the corresponding discretized eigenvalue problem. This kind of model for leaky Lamb waves with the analytically exact fluid interaction leads to a nonlinear eigenvalue problem, which is difficult to solve. We present a change in variables that yields an equivalent polynomial eigenvalue problem. The latter can be rewritten as a linear eigenvalue problem in state space. As a result, conventional numerical eigenvalue solvers can be used to robustly determine the sought wavenumbers. In contrast to traditional root-finding of the characteristic equations, the presented method guarantees to find all solutions and naturally handles complex wavenumbers. Additionally, no initial guesses for the wavenumbers are required.

Calculating the full leaky Lamb wave spectrum with exact fluid interaction - Kiefer, Daniel A.; Ponschab, Michael; Rupitsch, Stefan; Mayle, Michael (Journal of the Acoustical Society of America, 2019)
Lamb waves are elastodynamic guided waves in plates and are used for non-destructive evaluation, sensors, and material characterization. These applications rely on the knowledge of the dispersion characteristics, i.e., the frequency-dependent wavenumbers. The interaction of a plate with an adjacent fluid leads to a nonlinear differential eigenvalue problem with a square root term describing exchange of energy with the surrounding medium, e.g., via acoustic radiation. In this contribution, a spectral collocation scheme is applied to discretize the differential eigenvalue problem. A change of variable is performed to obtain an equivalent polynomial eigenvalue problem of fourth order, which is linear in state-space and can reliably be solved using modern numerical methods. Traditionally, the leaky Lamb wave problem has been solved by finding the roots of the characteristic equations, a numerically ill-conditioned problem. In contrast to root-finding, the approach described in this paper is inherently able to find all modes and naturally handles complex wavenumbers. The full phase velocity dispersion diagram and attenuation curves are presented and are shown to be in excellent agreement with solutions of the characteristic equation as well as computations made with a perturbation method. The procedure is applicable to anisotropic, viscoelastic, inhomogeneous, and layered plates coupled to an inviscid fluid.

Simulation-Based Characterization of Mechanical Parameters and Thickness of Homogeneous Plates Using Guided Waves - Ponschab, Michael; Kiefer, Daniel A.; Rupitsch, Stefan (IEEE Transactions on Ultrasonics Ferroelectrics and Frequency Control, 2019)
Properties of isotropic plates in terms of material constants and thickness are characterized by making use of dispersion characteristics of propagating Lamb waves. A numerical model is inversely optimized in order to match dispersion curves measured by laser vibrometry. This kind of material characterization gained interest in resent research. Improvements in accuracy and in efficiency of the optimization process are thereby important steps towards an industrial application of this technique to non-destructive testing and online monitoring. For this purpose, the use of a fast converging numerical model based on spectral collocation has been found to be well suited. Furthermore, we improved the signal to noise ratio by utilizing long time broadband excitation signals for multimodal excitation of Lamb waves. The wavenumber spectrum up to 2.5MHz is acquired by measurements with a laser-scanning-vibrometer. In order to exploit the information contained in higher order modes, we present an algorithm to match the measured data to the calculated modes during the optimization process, leading to higher accuracy of the estimated model parameters. The characterization results are verified by comparison to measurements with a conventional ultrasonic metho
Keywords: Ultrasound; Guided Waves; Lamb Waves; Spectral Method; Inverse Method; Material Characterization

The Influence of Temperature on the Frequency Dependent Directivity of Ultrasonic Transducers - An Indirect Acquisition Technique - Ponschab, Michael; Kiefer, Daniel A.; Rupitsch, Stefan (Sensoren und Messsysteme Beiträge der 19. ITG/GMA-Fachtagung, 2018)
Components of ultrasonic measurement devices suffer from exposition to temperature fluctuations, which influence both the speed of sound in the surrounding medium and the material properties of the ultrasonic transducer itself. A consequence may be deviations of the frequency response and the frequency dependent directivity pattern. This might have an undesirable impact, for instance, on the accuracy of flow metering devices. A conventional method for the determination of radiation patterns of water-coupled ultrasonic transducers is the scanning of the sound field with a hydrophone. Using this technique for the purpose of measuring influences of temperature would be challenging and time consuming. The required water basin, which represents a large thermal capacity, must be kept on stepwise constant temperatures. Furthermore, the hydrophone might not be designed for such conditions. The approach presented in this contribution exploits an indirect acquisition of the directivity. Instead of simulating the unknown ultrasonic transducer setup the normal velocity of the transducer surface is measured in air with a Laser-Scanning-Doppler-Vibrometer. In a second step, the acquired normal velocity serves as excitation signal for a finite-element simulation of the radiated sound field. The influence of temperature on the transducer is studied by recording the corresponding membrane vibrations while placing the transducer in a climatic chamber. The temperature dependent speed of sound of water is taken into account during simulation. For sake of validation, a comparison to hydrophone measurements at room temperature reveals good agreement of the frequency response at zero angle. The resulting directional patterns also exhibit distinctive similaritie
Keywords: ultrasound; ultrasonic transducers; beam pattern; measurement; temperature; directivity; acquisition technique

Towards an Inverse Characterization of Third Order Elastic Constants Using Guided Waves - Ponschab, Michael; Kiefer, Daniel A.; Rupitsch, Stefan (IEEE International Ultrasonics Symposium, IUS, 2019)
The acoustoelastic effect describes the change in propagation velocities of elastic waves due to mechanical prestress and is based on geometric and material nonlinearity. Models describing the effect heavily depend on the knowledge of the third order elastic constants (TOEC). Established acquisition methods of these constants rely on the measurement of bulk speeds of sound and analytic calculations. In this contribution, we propose an alternative method by making use of the dispersive character of guided waves in plates. Uniaxial tensile stress is applied to homogeneous metallic plates. The changes in wavenumber are calculated from laser vibrometer aided measurements. These changes depend on a trigonometric function of the direction of wave propagation and increase linearly with the prestress amplitude. Using this prior knowledge, we perform an inverse characterization of the TOEC by iteratively fitting a numerical model of the prestressed waveguide to constants of the trigonometric relation. The proposed method is verified using simulated reference data.
CRIS-Team Scopus Importer:2020-02-21
Keywords: acoustoelasticity; inverse method; Lamb wave; material characterization; nonlinear acoustics